A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS DARUL HIKMAH PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Andini, Desi; Eliwarti, Eliwarti; Supriusman, Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study is entitled “A Study on the Ability of the Second Year Students of MTs Darul Hikmah Pekanbaru in Writing Descriptive Texts. This study concerns with five aspects of writing. They are grammar, vocabulary, mechanic, organization, and fluency. The aim of this study is to find out the ability level of the second-year students of MTs Darul Hikmah Pekanbaru in writing descriptive texts. The data collecting technique is using a writing test. The students’ writing results are checked and scored by the expert. The research findings are as follows: first, the ability of the second-year students in writing descriptive texts is in good level with the average score of 78.81. Second, the students’ average score in terms of Organization is 17.12, and in terms of Contents is 16.21, in terms of Mechanic is 16.27, in terms of Vocabulary is 15.30, and in terms of Grammar is 13.90. based on these findings, it is found that grammar is the most difficult problem faced by the students in writing descriptive texts. All in all, findings show that the the second-year students of MTs Darul Hikmah Pekanbaru have relatively good level in writing descriptive texts. However, they need to practice more in writing a text for the betterment of the study.Key Words: Ability, Descriptive Texts, Writing,